(untitled) (Sirte Journal of Medical Sciences, 2023)
This study was performed to examine the predictive factors of pathologic complete response (pCR) in locally advanced breast cancer (LABC) patients after neoadjuvant chemotherapy (NAC). LABC remains a clinical challenge, as distant metastasis develops in most patients, and they will experience disease relapse and eventual death. The identification of reliable predictive factors for neoadjuvant chemotherapy in LABC would help select those patients most likely to benefit from neoadjuvant chemotherapy. 84 LABC Egyptian patients with neoadjuvant therapy regimens containing 3-6 cycles of anthracyclin-based chemotherapy, followed by modified radical mastectomy (MRM) and node dissections, followed by adjuvant hormonal therapy and Radiotherapy.The patients were divided into two groups: pathological complete response (pCR) or non-pCR group. Clinico-pathological characteristics were compared and analyzed, and multivariate analyses were performed to detect the predictive factors of pCR. The pCR rate in both the breast and axilla was (8.33%), and 91.67% of the patients showed partial response. Multivariate logistic regression demonstrated that pCR was significantly associated with The absence of nodal metastasis, necrosis, lymphovascular invasion and carcinoma in situ and negative ER , PR and HER2 and the non-triple negative tumours. the absence of tumor necrosis, DCIS and LVI and negative hormonal status on initial core biopsy are linked to achieving pCR